Modeling cytoadhesion of Plasmodium falciparum-infected erythrocytes and leukocytes: common principles and distinctive features - Helms, Gesa; Dasanna, Anil Kumar; Schwarz, Ulrich S.; Lanzer, Michael (FEBS letters, 2016)
Cytoadhesion of Plasmodium falciparum-infected erythrocytes to the microvascular endothelial lining shares striking similarities to cytoadhesion of leukocytes. In both cases, adhesins are presented in structures that raise them above the cell surface. Another similarity is the enhancement of adhesion under physical force (catch bonding). Here, we review recent advances in our understanding of the molecular and biophysical mechanisms underlying cytoadherence in both cellular systems. We describe how imaging, flow chamber experiments, single-molecule measurements, and computational modeling have been used to decipher the relevant processes. We conclude that although the parasite seems to induce processes that resemble the cytoadherence of leukocytes, the mechanics of erythrocytes is such that the resulting behavior in shear flow is fundamentally different.